Metal organic framework nano sandwich composite material as well as preparation method and application thereof

The two-dimensional sheet material and metal organic frame nanoparticles are assembled on the surface of the solvent crystal through the limited-domain freezing assembly method to form a nanosandwich structure, which solves the problem of insufficient stability of MOF materials, achieves higher chemical and thermal stability, and efficiently captures CO2 in humid environments.

CN119842237APending Publication Date: 2025-04-18INST OF CHEM CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311350448.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Metal organic frame (MOF) materials are susceptible to environmental factors during synthesis and practical application, resulting in reduced stability, poor service life and effect.

Method used

The limited-domain freezing assembly method is used to accurately assemble two-dimensional sheet-like materials and nanonuclear materials (such as metal organic frame nanoparticles or nanosheets) on the surface of the solvent crystal to form a nanosandwich structure.

Benefits of technology

Improves the stability of MOF materials, enhances their chemical, thermal and mechanical stability while maintaining their original properties, especially in humid environments to effectively capture CO2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842237A_ABST
    Figure CN119842237A_ABST
Patent Text Reader

Abstract

The invention discloses a metal organic framework nano sandwich composite material as well as a preparation method and application thereof. The metal organic framework nano sandwich composite material comprises a two-dimensional sheet material and a nano core material, wherein the two-dimensional sheet material is accurately assembled on the outer surface of the nano core material on the nanoscale; the nanometer core material is accurately assembled between the two pieces of two-dimensional sheet-shaped materials, and the two pieces of two-dimensional sheet-shaped materials are accurately assembled on the outer surface of the nanometer core material on the nanometer scale to form a nanometer sandwich structure. The two-dimensional sheet material and the metal organic framework particles form a sandwich structure, so that the stability of the metal organic framework is improved, a new direction is provided for improving the stability of the metal organic framework, and the method has very positive influence on industrial application of the metal organic framework in the fields of separation, catalysis, energy storage, sensing and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention provides a metal organic framework nano sandwich composite material prepared by a confined freeze assembly method and its application, which improves the stability of MOF and is especially successfully applied to the capture of CO2 in moist flue gas. Background Art

[0002] Metal-organic framework (MOF) materials are porous materials with special structures and functions, and have broad application prospects, such as separation, energy storage, catalysis, etc. However, the challenges faced by MOF materials include: the synthesis of MOF materials requires precise control of conditions and the composition of reaction intermediates, otherwise it may lead to impure products or difficulty in producing the desired products; MOF materials are easily affected by environmental factors (such as moisture, high temperature, etc.) during actual application and lose stability, reducing their service life and effectiveness.

[0003] Conventional post-synthesis modification methods for MOF materials mainly include the following: surface modification, framework modification, pore modification, and covalent modification. By introducing specific functional groups or modifiers, the material properties can be regulated. Common strategies include alkylation, phosphorylation, silicification, metal ion exchange, and ligand replacement. However, conventional post-synthesis modification strategies also have some defects that need to be overcome: some modification methods may introduce new functional groups or change the structure of MOF materials; during the modification process, the introduced functional groups or modifiers may bring in impurities; some modification methods may be unstable under environmental conditions, resulting in the weakening of the modification effect over time; some modification methods may have certain restrictions on the structure and properties of MOF materials, making specific modification goals difficult to achieve. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0005] A metal organic framework nano sandwich composite material, the metal organic framework nano sandwich composite material comprising a two-dimensional sheet material and a nano core material, the two-dimensional sheet material is precisely assembled on the outer surface of the nano core material at the nano scale; the nano core material is precisely assembled between two two-dimensional sheet materials, and the two two-dimensional sheet materials are precisely assembled on the outer surface of the nano core material at the nano scale to form a nano sandwich structure;

[0006] The nanocore material is a metal organic framework nanoparticle or a metal organic framework nanosheet.

[0007] Preferably, the size of the two-dimensional sheet material is not smaller than the size of the nano-core material.

[0008] According to an embodiment of the present invention, the metal organic framework nano sandwich composite material comprises at least two two-dimensional sheet materials and one nano core material, and the two two-dimensional sheet materials completely or partially wrap the outer surface of the nano core material.

[0009] According to an embodiment of the present invention, in the metal-organic framework nano sandwich composite material, the two-dimensional sheet material is a solvent-dispersed two-dimensional sheet material.

[0010] According to an embodiment of the present invention, the two-dimensional sheet material is selected from flexible two-dimensional sheet materials such as graphene oxide nanosheets, graphene nanosheets, graphyne nanosheets, copper oxide nanosheets, and MXene.

[0011] According to an embodiment of the present invention, the size of the two-dimensional sheet material is 1-2 times, for example, 1 time or 1.5 times, the size of the nano-core material.

[0012] According to an embodiment of the present invention, the size of the two-dimensional sheet material is not greater than 5μm, for example, 0.1-5μm, and for example, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 2μm, 3μm, 4μm, and 5μm.

[0013] According to an embodiment of the present invention, the two-dimensional sheet material may be a single-layer and / or few-layer structure.

[0014] According to an embodiment of the present invention, the metal organic framework nanoparticles or metal organic framework nanosheets can be made of metal organic framework materials known in the art, for example, selected from ZIF-8, HKUST-1, UiO-66, and MOF-5.

[0015] According to an embodiment of the present invention, the size of the nano-core material is not greater than 3 μm, preferably 0.1-3 μm, for example 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 2 μm, 3 μm. When the size is greater than 3 μm, the particles or nano-sheets of the nano-core material are easily precipitated.

[0016] According to an embodiment of the present invention, the two-dimensional sheet material is combined with the nano-core material by using hydrophilic and hydrophobic and / or electrostatic interactions as driving forces.

[0017] According to an embodiment of the present invention, the molar ratio of the two-dimensional sheet material to the nanocore material is (2-3):1, for example, 2.5:1, preferably 2:1.

[0018] According to an embodiment of the present invention, the precise assembly refers to assembly by confined freezing on the surface of a solvent crystal, specifically comprising: firstly, rapidly mixing a dispersion of the nanocore material and a dispersion of the two-dimensional sheet material, and then quenching at a low temperature to form a solvent crystal, in which the two-dimensional sheet material and the nanocore material are dispersed; then, the solvent crystal is annealed, and as the solute is enriched at the interface, a confined space is formed on the surface of the solvent crystal, and the nanocore material and the two-dimensional sheet material are precisely assembled on the nanoscale in the confined space and / or on the surface of the solvent crystal, and the nanocore material is wrapped between two two-dimensional sheet materials to obtain the nano sandwich structure.

[0019] According to an embodiment of the present invention, the dispersion liquid of the nano-core material and the dispersion liquid of the two-dimensional sheet material contain at least a solvent, and the solvent is quenched at a low temperature to form solvent crystals.

[0020] According to an embodiment of the present invention, the solvent is selected from water and / or a polar solvent. Preferably, the polar solvent is selected from a polar solvent miscible with water. Preferably, the polar solvent is, for example, selected from at least one of ethanol, methanol, dimethylformamide (DMF), dichloromethane (DCM), ethyl acetate, and chloroform.

[0021] Preferably, the solvent is selected from water and polar solvents, and the surface of the solvent crystal formed by the solvent crystal has a preferential adsorption on the two-dimensional sheet material. Therefore, in the process of confined freeze assembly, the two-dimensional sheet material is first adsorbed on the surface of the solvent crystal, and the core material is driven by hydrophilic and hydrophobic and / or electrostatic effects to combine with the nanosheet material to achieve precise assembly, and the solvent crystal plays a template role. In the present invention, by adjusting the initial concentration of the two-dimensional sheet material and the nanocore material and the confined effect of the solvent crystal, the aggregation phenomenon of the two-dimensional sheet material or the nanocore material is effectively avoided.

[0022] According to an embodiment of the present invention, the shape of the nano-core material is, for example, at least one selected from a polyhedron, a sheet, and a multilayer structure.

[0023] According to an embodiment of the present invention, the metal organic framework nano sandwich composite material is a monodisperse particle. In the present invention, the monodisperse particle refers to a nanoparticle or a two-dimensional sheet material that can achieve single dispersion at the nanoscale.

[0024] According to an embodiment of the present invention, the metal organic framework nano sandwich composite material has better fluidity, fillability and specific surface area.

[0025] According to an embodiment of the present invention, compared with the original metal organic framework material, the metal organic framework nano sandwich composite material has higher stability, for example, has enhanced chemical stability, thermal stability and mechanical stability.

[0026] The present invention also provides a method for preparing the metal organic framework nano sandwich composite material. The method for preparing the metal organic framework nano sandwich composite material comprises:

[0027] Step 1: dispersing the nanocore material in a first solvent to obtain a dispersion of the nanocore material, and dispersing the two-dimensional sheet material in a second solvent to obtain a dispersion of the two-dimensional sheet material;

[0028] Step 2: quickly mixing the dispersion of the two-dimensional sheet material and the dispersion of the nanocore material in step 1 to obtain a mixed solution, and quenching at low temperature to form a mixed solvent crystal; the two-dimensional sheet material and the nanocore material are dispersed in the solvent crystal;

[0029] Step 3: Annealing the mixed solvent crystals obtained in step 2 to mature the solvent crystals; at this time, with the interfacial enrichment of the solute, a confined space is formed on the surface of the solvent crystal, and the two-dimensional sheet material and the nanocore material are dispersed in the confined space and / or on the surface of the solvent crystal, achieving precise assembly at the nanoscale to obtain the metal organic framework nano sandwich composite material.

[0030] According to an embodiment of the present invention, in step 1, in the dispersion of the MOF nanocore material, the concentration of the nanocore material is not specifically limited, as long as the metal organic framework nano sandwich composite material can be obtained. Exemplarily, the concentration of the metal organic framework nanoparticles or metal organic framework nanosheets is 0.01-0.1 mg / ml; if the concentration is too high, the yield of the prepared metal organic framework nano sandwich composite material will be reduced; if the concentration is too low, the efficiency of preparing the metal organic framework nano sandwich composite material is too low.

[0031] According to an embodiment of the present invention, in step 1, the nanocore material has the meaning as described above, for example, metal organic framework nanoparticles or metal organic framework nanosheets.

[0032] According to an embodiment of the present invention, the metal organic framework nanoparticles or metal organic framework nanosheets can be selected from metal organic framework materials known in the art, for example, selected from ZIF-8, HKUST-1, UiO-66, MOF-5, etc.

[0033] According to an embodiment of the present invention, the size of the nano-core material is not greater than 3 μm, preferably 0.1-3 μm, for example 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 2 μm, 3 μm. When the size is greater than 3 μm, the particles or nano-sheets of the nano-core material are easily precipitated.

[0034] According to an embodiment of the present invention, in step 1, the first solvent is selected from a polar solvent. Preferably, the polar solvent is selected from at least one of ethanol, methanol, dimethylformamide (DMF), dichloromethane (DCM), ethyl acetate, and chloroform.

[0035] According to an embodiment of the present invention, in step 1, the second solvent is selected from water and / or a polar solvent. Preferably, the polar solvent is selected from at least one of ethanol, methanol, dimethylformamide (DMF), dichloromethane (DCM), ethyl acetate, and chloroform.

[0036] According to an embodiment of the present invention, in step 1, when the second solvent is selected from a polar solvent, the first solvent and the second solvent may be the same or different. Exemplarily, when the nanocore material is selected from metal organic framework nanoparticles or metal organic framework nanosheets, the first solvent is selected from a polar solvent (such as methanol, ethanol), and the second solvent is selected from water. For example, ethanol and water are mixed in a volume ratio of 1:9 to obtain an ethanol aqueous solution with a volume fraction of 10%, and its freezing point is about -4.5°C; for example, ethanol and water are mixed in a volume ratio of 2:8 to obtain a 20% ethanol aqueous solution, and its freezing point is about -8 to -9°C.

[0037] According to an embodiment of the present invention, in step 2, the low-temperature quenching refers to rapid cooling at a temperature lower than the annealing temperature (such as -30°C) to obtain solvent crystals, and liquid nitrogen or a -80°C low-temperature refrigerator can be commonly used.

[0038] According to an embodiment of the present invention, in step 2, the low-temperature quenching can be performed in a manner known in the art, such as in liquid nitrogen or a low-temperature refrigerator.

[0039] According to an embodiment of the present invention, in step 2, the dispersion of the nanocore material and the dispersion of the two-dimensional sheet material are mixed in a manner selected from the first or second manner:

[0040] Method 1: quickly blending the dispersion of the nano-core material and the dispersion of the two-dimensional sheet material, and then quenching at low temperature to form the solvent crystals;

[0041] Method 2: Alternately dropping the dispersion of the nano-core material and the dispersion of the two-dimensional sheet material into a low-temperature environment in the form of droplets, and then quenching at low temperature to form the solvent crystals.

[0042] According to an embodiment of the present invention, in step 2, in the solvent crystal, the molar ratio of the two-dimensional sheet material to the nanocore material is (2-3):1, preferably 2:1.

[0043] According to an embodiment of the present invention, in step 2, the concentration of the nanocore material in the solvent crystal is not specifically limited, as long as the metal organic framework nano sandwich composite material can be prepared, for example, 0.01 mg / ml-0.1 mg / ml.

[0044] According to an embodiment of the present invention, in step 2, in the solvent crystal, the size of the two-dimensional sheet material is not less than the size of the nanocore material. Preferably, the size of the two-dimensional sheet material is 1 to 2 times the size of the nanocore material.

[0045] According to an embodiment of the present invention, in step 3, during the aging process, the solvent crystals are recrystallized, that is, the smaller solvent crystals dissolve and are deposited again on the larger solvent crystals, and a confined space is formed on the surface of the solvent crystals due to the interfacial enrichment of the solute. As the recrystallization continues, the concentration of the two-dimensional sheet material and the nanocore material in the confined space and / or on the surface of the solvent crystal gradually increases, and the metal organic framework nano sandwich composite material is obtained by precise assembly.

[0046] According to an embodiment of the present invention, in step 3, the treatment conditions include: constant temperature annealing for a period of time at an annealing temperature. Preferably, the annealing temperature does not exceed the solidification point T of the mixed solution, and is preferably 5 to 30°C lower than the solidification point T of the mixed solution; illustratively, the annealing temperature is between T-5°C and T-30°C, for example, T-10°C, T-20°C. Preferably, the annealing time is 45 minutes to 120 minutes, for example, 60 minutes, 90 minutes, 120 minutes. In the present invention, the solidification point of the mixed solution refers to the solidification point after the first solvent and the second solvent are mixed. In the present invention, the higher the annealing temperature, the faster the ripening of the solvent crystals, and the shorter the required annealing time. In the present invention, the nano-core material and the two-dimensional sheet material are precisely assembled in the confined space provided by the solvent crystal and / or on the surface of the solvent crystal. By simply controlling the appropriate annealing temperature, the mixed crystal can be prevented from ripening too fast, thereby avoiding the aggregation of the two-dimensional sheet material and / or the nano-core material.

[0047] According to an embodiment of the present invention, in step 3, the annealing treatment can be carried out under conditions known in the art, such as in a refrigerator or a cold storage.

[0048] According to an embodiment of the present invention, the preparation method further comprises: Step 4: further removing the solvent crystals to obtain the metal organic framework nano sandwich composite material.

[0049] According to an embodiment of the present invention, in step 4, removing the solvent crystals is specifically drying.

[0050] According to a preferred embodiment of the present invention, the drying may be carried out by a drying method known in the art, such as at least one or more selected from atmospheric pressure drying, reduced pressure drying, freeze drying or supercritical drying.

[0051] According to an embodiment of the present invention, in step 4, solvent replacement may be performed first to obtain solvent crystals that are easier to remove, and then the solvent crystals may be removed by the above-mentioned drying method or the like.

[0052] According to an exemplary embodiment of the present invention, the method for preparing the metal organic framework nano sandwich composite material comprises:

[0053] S1: Select a two-dimensional sheet material (such as graphene oxide nanosheets) with an average size of 0.5 μm and a nanocore material (such as metal organic framework particles, preferably ZIF-8, HKUST-1, UiO-66) with a size of 0.1-0.5 μm (for example, 0.4 μm), disperse the nanocore material in ethanol to obtain a dispersion of the nanocore material at a concentration of 0.1 mg / ml; disperse the two-dimensional sheet material in water to obtain a dispersion of the two-dimensional sheet material at a mass fraction of 5 wt%, and the volume ratio of ethanol to water is 1:9;

[0054] S2: Alternately dropping the dispersion of the nanocore material and the dispersion of the two-dimensional sheet material in S1 into a low-temperature environment by means of microdroplets, and forming mixed solvent crystals by low-temperature quenching;

[0055] S3: raising the temperature to -20°C and annealing for 45 minutes, so that the mixed solvent crystals are ripened, the two-dimensional sheet material and the nano-core material are enriched in the confined space formed on the surface of the mixed solvent crystals, and the metal organic framework nano sandwich composite material is precisely assembled in the confined space and / or on the surface of the solvent crystals;

[0056] S4: The mixed solvent crystals are removed by freeze drying to obtain a monodisperse metal-organic framework nano-sandwich composite.

[0057] The present invention also provides applications of the above metal organic framework nano sandwich composite material, such as applications in the fields of separation, catalysis, energy storage, catalysis, photonics and sensing, and for example, applications in the field of flue gas (such as CO2) adsorption.

[0058] Beneficial Effects

[0059] The present invention provides a method and application for improving the stability of a metal organic framework without reducing its own performance. The present invention uses a metal organic framework and a two-dimensional sheet material to confine the metal organic framework between solvent crystal particles, so that the metal organic framework, such as a metal organic framework particle, is coated between two-dimensional sheet materials of comparable size, such as graphene oxide nanosheets. Calculations show that due to the low coordination number of the metal organic framework, its degradation starts from the crystal surface. Since the two-dimensional sheet material can be tightly combined with the metal organic framework surface, the two-dimensional sheet material is like "armor" to resist the attack of various polar molecules and ions, thereby enhancing the thermal, mechanical and chemical stability of the metal organic framework. The nano sandwich structure of the metal organic framework nano sandwich composite material can be degraded from the unprotected micro surface, and some protonated organic ligands released by the metal organic framework nano sandwich composite material during the degradation process will be enriched near its unprotected surface; these protonated organic ligands can resist the attack of polar molecules and ions, thereby stabilizing the unprotected metal organic framework surface. It has been verified by gas penetration experiments that the metal organic framework nano sandwich composite material can efficiently and stably capture carbon dioxide in humid flue gas, further improving the adsorption performance.

[0060] Compared with conventional methods for improving the stability of metal-organic frameworks, the present invention improves the stability of metal-organic frameworks while retaining their original performance and does not reduce the adsorption capacity of the metal-organic frameworks. Using the method of confined freeze-assembly, the metal-organic framework can be encapsulated between two two-dimensional sheet materials of comparable size in a solvent crystal. The two-dimensional sheet material acts as "armor" to resist attacks from various polar molecules and ions, allowing the metal-organic framework nano-sandwich composite to maintain high stability. The metal-organic framework nano-sandwich composite can even effectively capture carbon dioxide from high-humidity flue gas while fully maintaining its crystallinity and porosity. This strategy is applicable to various metal-organic framework nanoparticles or nanosheets, so it is expected that this strategy will greatly promote the practical application of metal-organic frameworks.

[0061] The present invention provides an idea and principle for improving the stability of metal-organic frameworks by forming a sandwich structure between two-dimensional sheet materials and metal-organic framework particles, which provides a new direction for improving the stability of metal-organic frameworks and has a very positive impact on the industrial applications of metal-organic frameworks in the fields of separation, catalysis, energy storage, and sensing. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1-1 This is a scanning electron microscope image of the metal-organic framework nano sandwich composite material of Example 1.

[0063] Figure 1-2 This is the powder X-ray diffraction pattern of the metal-organic framework nano sandwich composite material of Example 1.

[0064] Figure 2 This is a laser confocal microscopy image of the metal-organic framework nano-sandwich composite material of Example 2.

[0065] Figure 3 This is a powder X-ray diffraction pattern of the metal organic framework nano sandwich composite material of Example 3, characterizing its chemical stability.

[0066] Figure 4-1 This is the temperature-dependent powder X-ray diffraction pattern of metal-organic framework nanostructures (HKUST-1).

[0067] Figure 4-2 This is the temperature-dependent powder X-ray diffraction pattern of the metal-organic framework nano sandwich composite material HKUST-1-GO of Example 3, characterizing its thermal stability.

[0068] Figure 5-1 Cyclic stability of the metal-organic framework HKUST-1 for CO2 capture applications.

[0069] Figure 5-2 Cyclic stability of metal-organic framework nano-sandwich composite HKUST-1-GO for CO2 capture applications. DETAILED DESCRIPTION

[0070] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0071] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0072] Example 1

[0073] The preparation process of ZIF-8-GO metal organic framework nano sandwich composites is as follows:

[0074] Step 1: Disperse ZIF-8 with an average size of about 0.5 μm in ethanol to obtain a 0.1 mg / ml MOF dispersion; disperse graphene oxide nanosheets (GO) with an average size of 0.5 μm in water to obtain a 5 wt% GO dispersion; wherein the volume ratio of ethanol to water is 1:9;

[0075] Step 2: Alternately drop the above two dispersions into a low-temperature container at -80°C by microdroplet method for low-temperature quenching to form fine mixed solvent crystals, in which GO and ZIF-8 are dispersed;

[0076] Step 3: Raise the temperature in the cryogenic container to -20°C for annealing for 45 minutes to ripen the finely divided mixed solvent crystals. During the ripening process, the smaller solvent crystals dissolve and deposit again on the larger solvent crystals. With the interfacial enrichment of the solute, a confined space is formed on the surface of the solvent crystal. The concentrations of GO and ZIF-8 in the confined space increase. GO and ZIF-8 are assembled in the confined space of the solvent crystal and / or on the surface of the solvent crystal to obtain a metal organic framework nano sandwich composite material having a nano sandwich structure.

[0077] Step 4: The solvent crystals in the above system are removed by freeze-drying to obtain a monodispersed ZIF-8-GO metal organic framework nano sandwich composite material.

[0078] Example 2

[0079] The preparation process of the UiO-66-GO metal organic framework nano sandwich composite material is similar to that of Example 1, except that:

[0080] In step 1, ZIF-8 was replaced with UiO-66 to obtain a MOF dispersion;

[0081] In step 2, the two dispersions obtained in step 1 of this embodiment are alternately dropped into a low-temperature container at -80°C by microdroplet method for low-temperature quenching to form fine mixed solvent crystals, and GO and UiO-66 are dispersed in the solvent crystals;

[0082] Steps 3 and 4 are basically the same as in Example 1, and a monodispersed UiO-66-GO metal organic framework nano sandwich composite material is prepared.

[0083] Example 3

[0084] The preparation process of HKUST-1-GO metal organic framework nano sandwich composite material is similar to that of Example 1, except that:

[0085] In step 1, ZIF-8 was replaced with HKUST-1 to obtain a MOF dispersion;

[0086] In step 2, the two dispersions obtained in step 1 of this embodiment are alternately dropped into a low-temperature container at -80°C by microdroplet method for low-temperature quenching to form fine mixed solvent crystals, thereby obtaining GO and HKUST-1 dispersed in the solvent crystals;

[0087] Steps 3 and 4 are basically the same as in Example 1, and a monodispersed HKUST-1-GO metal organic framework nano sandwich composite material is prepared.

[0088] Test Example 1

[0089] Figure 1-1It is a scanning electron microscope (SEM) image of the ZIF-8-GO metal organic framework nano sandwich composite material. It can be seen from Figure 1 that the average size of the ZIF-8-GO metal organic framework nano sandwich composite material prepared in this embodiment is 0.5 μm, and in the ZIF-8-GO metal organic framework nano sandwich composite material, ZIF-8 is coated between two GO nanosheets to form a monodisperse sandwich structure.

[0090] Figure 1-2 The powder X-ray diffraction pattern of ZIF-8-GO metal organic framework nano sandwich composite material is shown in Figure 2. Figure 1-2 It can be seen that the MOF-GO metal organic framework nano sandwich composite material prepared in this embodiment is basically consistent with the X-ray diffraction pattern of ZIF-8. It can be seen that the MOF-GO metal organic framework nano sandwich composite material prepared in this embodiment hardly affects the original crystal properties of ZIF-8.

[0091] Figure 2 This is a laser confocal microscopic image of the metal organic framework nano sandwich composite material of Example 2. The average size of the metal organic framework nano sandwich composite material is 0.5 μm.

[0092] Figure 3 The figure is the powder X-ray diffraction pattern of the metal organic framework nano sandwich composite material of Example 3, and the X-ray diffraction patterns of HKUST-1 and HKUST-1-GO were tested after being stored in water for 3 days and 7 days, respectively, and recorded as HKUST-1 (water, 3 days) and HKUST-1-GO (water, 7 days). By comparison, it can be seen that the crystallinity of HKUST-1-GO is not lost after being immersed in water; while the crystallinity of HKUST-1 is destroyed after being immersed in water. It can be seen that the HKUST-1-GO metal organic framework nano sandwich composite material has significantly enhanced water stability.

[0093] The powder X-ray diffraction patterns of HKUST-1 at different temperatures were tested by variable temperature XRD. Figure 4-1 and Figure 4-2 As shown, it can be seen that the thermal stability of the HKUST-1-GO metal-organic framework nano-sandwich composite is enhanced.

[0094] The above tests show that the metal organic framework nano sandwich composite materials prepared in Examples 2 and 3 have a nano sandwich structure similar to that of Example 1, that is, UiO-66 or HKUST-1 is used as the core material, and GO is used as a two-dimensional sheet material coated on the outer surface of the core material at the nanoscale. The metal organic framework nano sandwich composite material of the present invention hardly affects the original crystal properties of the core materials such as ZIF-8, UiO-66 or HKUST-1, and has higher chemical stability and thermal stability.

[0095] Application Example 1

[0096] The CO2 adsorption capacity of the metal organic framework nano sandwich composite material prepared in the above examples 1-3 was tested by the following specific method:

[0097] At 298K, 1bar, 75% RH, a penetration experiment of CO2 / N2 separation was carried out. The metal organic framework nano sandwich composite materials of the above Examples 1-3 were used as samples and crushed into particles after compression at 3MPa, and sieved to obtain small particles of 40-60 mesh, which were recorded as ZIF-8-GO, UiO-66-GO, and HKUST-1-GO respectively. The samples were activated under high vacuum (10-6bar) at 393K for 6 hours. The activated particles of ZIF-8-GO, UiO-66-GO, and HKUST-1-GO were placed in a stainless steel column (internal dimensions 4×75mm). Before the experiment, the column was purged with Ar gas at a flow rate of 100mL / min at 353K for 1h, and then a CO2 / N2 (15 / 85, v / v) mixed gas separation experiment was carried out at a flow rate of 5mL / min (298K, 1.01bar) at 75% relative humidity. The eluting gas mixture was monitored by gas chromatography with a thermal conductivity detector (Agilent-490 Micro GC).Before each cycle experiment, the stainless steel column was regenerated by flowing argon gas through the column at a rate of 100 mL / min for 30 min at room temperature.

[0098] exist Figure 5-1 and Figure 5-2 It can be seen that the stability (such as water stability or thermal stability) of water-sensitive MOF (such as HKUST-1) is greatly improved after the metal organic framework nano sandwich composite material is obtained by the preparation method of the present invention, and it has the ability to capture CO2 in a humid environment and has excellent cycle performance. The present invention prepares the metal organic framework nano sandwich composite material by putting GO as "armor" on MOF, which provides a broad application prospect for the industrial application of MOF and broadens the road for the fields of separation, catalysis, energy storage and other fields of MOF.

[0099] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A metal organic framework nano sandwich composite material, characterized in that: The metal organic framework nano sandwich composite material comprises a two-dimensional sheet material and a nano core material, wherein the two-dimensional sheet material is precisely assembled on the outer surface of the nano core material at the nano scale; the nano core material is precisely assembled between two two-dimensional sheet materials, and the two two-dimensional sheet materials are precisely assembled on the outer surface of the nano core material at the nano scale to form a nano sandwich structure; The nanocore material is a metal organic framework nanoparticle or a metal organic framework nanosheet; The size of the two-dimensional sheet material is not less than the size of the nano-core material.

2. The metal organic framework nano sandwich composite material according to claim 1, characterized in that: The metal organic framework nano sandwich composite material comprises at least two two-dimensional sheet materials and one nano core material, and the two two-dimensional sheet materials completely or partially wrap the outer surface of the nano core material. Preferably, in the metal-organic framework nano sandwich composite material, the two-dimensional sheet material is a solvent-dispersed two-dimensional sheet material. Preferably, the two-dimensional sheet material is selected from flexible two-dimensional sheet materials such as graphene oxide nanosheets, graphene nanosheets, graphyne nanosheets, copper oxide nanosheets, and MXene.

3. The metal organic framework nano sandwich composite material according to claim 1 or 2, characterized in that: The size of the two-dimensional sheet material is 1-2 times the size of the nano-core material. Preferably, the size of the two-dimensional sheet material is no greater than 5 μm. Preferably, the two-dimensional sheet material is a single-layer and / or few-layer structure. Preferably, the size of the nano-core material is no greater than 3 μm. Preferably, the two-dimensional sheet material is combined with the nano-core material by using hydrophilic and hydrophobic and / or electrostatic interactions as driving forces. Preferably, the molar ratio of the two-dimensional sheet material to the nanocore material is (2-3):

1.

4. The metal organic framework nano sandwich composite material according to any one of claims 1 to 3, characterized in that: The dispersion liquid of the nano-core material and the dispersion liquid of the two-dimensional sheet material contain at least a solvent, and the solvent is quenched at a low temperature to form a solvent crystal. Preferably, the solvent is selected from water and / or polar solvents. Preferably, the shape of the nano-core material is selected from at least one of a polyhedron, a sheet, and a multilayer structure.

5. The metal organic framework nano sandwich composite material according to any one of claims 1 to 4, characterized in that: The metal organic framework nano sandwich composite material is monodispersed particles. Preferably, the metal organic framework nano sandwich composite material has better fluidity, fillability and specific surface area. Preferably, compared with the original metal organic framework material, the metal organic framework nano sandwich composite material has higher stability.

6. The method for preparing the metal organic framework nano sandwich composite material according to any one of claims 1 to 5, the method for preparing the metal organic framework nano sandwich composite material comprising: Step 1: dispersing the nanocore material in a first solvent to obtain a dispersion of the nanocore material, and dispersing the two-dimensional sheet material in a second solvent to obtain a dispersion of the two-dimensional sheet material; Step 2: quickly mixing the dispersion of the two-dimensional sheet material and the dispersion of the nano-core material in step 1 to obtain a mixed solution, and quenching at low temperature to form a mixed solvent crystal; the two-dimensional sheet material and the nano-core material are dispersed in the solvent crystal; Step 3: annealing the mixed solvent crystals obtained in step 2 to mature the solvent crystals; at this time, with the interfacial enrichment of the solute, a confined space is formed on the surface of the solvent crystal, and the two-dimensional sheet material and the nanocore material are dispersed in the confined space and / or on the surface of the solvent crystal, achieving precise assembly at the nanoscale to obtain the metal organic framework nano sandwich composite material.

7. The preparation method according to claim 6, characterized in that: The size of the nano core material is no greater than 3 μm. Preferably, in step 1, the first solvent is selected from polar solvents. Preferably, in step 1, the second solvent is selected from water and / or a polar solvent. Preferably, in step 1, when the second solvent is selected from a polar solvent, the first solvent and the second solvent may be the same or different.

8. The preparation method according to claim 6 or 7, characterized in that: In step 2, the low temperature quenching refers to rapid cooling to obtain solvent crystals. Preferably, in step 2, the dispersion of the nanocore material and the dispersion of the two-dimensional sheet material are mixed in a manner selected from the first or second manner: Method 1: quickly blending the dispersion of the nano-core material and the dispersion of the two-dimensional sheet material, and then quenching at low temperature to form the solvent crystals; Method 2: Alternately dropping the dispersion of the nano-core material and the dispersion of the two-dimensional sheet material into a low-temperature environment in the form of droplets, and then quenching at low temperature to form the solvent crystals. Preferably, in step 2, in the solvent crystal, the molar ratio of the two-dimensional sheet material to the nanocore material is (2-3):

1. Preferably, in step 2, in the solvent crystal, the size of the two-dimensional sheet material is not less than the size of the nanocore material.

9. The preparation method according to any one of claims 5 to 8, characterized in that: In step 3, during the aging process, the solvent crystals are recrystallized, that is, the smaller solvent crystals are dissolved and redeposited on the larger solvent crystals, and as the solute is enriched at the interface, a confined space is formed on the surface of the solvent crystals. Preferably, in step 3, the treatment conditions include: constant temperature annealing at an annealing temperature for a period of time. Preferably, the preparation method further comprises: Step 4: further removing the solvent crystals to obtain the metal organic framework nano sandwich composite material.

10. Application of the metal organic framework nano sandwich composite material according to any one of claims 1 to 5 in the fields of separation, catalysis, energy storage, catalysis, photonics and sensing, and flue gas adsorption.